Congo Red as a Modifier for Amperometric Determination of Ascorbic Acid - Sabzi, R.E.; Minaei†, E.; Farhadi†, K. (Asian Journal of Chemistry, 2010)
In this paper, the fabrication and characterization of congo red chemically modified electrode are described. A carbon-paste electrode (CPE) chemically modified with the congo red was used as an electrochemical sensor for the determination of ascorbic acid. The electrochemical charac-terization of this modified electrode exhibits stable redox behaviour for congo red-CPE. The electrochemical behaviour of congo red-CPE was studied, using cyclic voltammetric, chronoamperometric, differential pulse voltammograms (DPV) and hydrodynamic amperometric techniques. The experimental results showed that ascorbic acid was electro-oxidized at the congo red modified carbon paste electrode. The electrode has shown a stable response in the longterm. At a fixed potential (0.6 V vs. SCE) under stirred conditions, the calibration plot was linear over the ascorbic acid concentration range 50-6000 μM. The detection limit of the method is 29 μM. The relative standard deviation for 60 μM ascorbic acid (3 repetitions using the same electrode) is 4.3 %.